2014
DOI: 10.1590/s0102-86502014001400005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial and antitumoral activity of Garcinia mangostana L. (mangosteen) grown in Southeast Brazil

Abstract: RESULTS:Our results showed many secretory canals in resin fruit and leaf; identifying lipids, starch, lignin and phenolic compounds.The leaf extract induced genotoxicity and apoptosis in B16-F10 cells, since the fragmentation of DNA in the comet assay. The ethanolic extract of mangosteen obtained in the resin, leaf and fruit showed antimicrobial activity against Staphylococcus aureus and Escherichia coli with a MIC at 0.1 mg/mL. CONCLUSION:In conclusion, we have demonstrated both antimicrobial and antitumor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Another study by Kaur and co-workers showed that eugenol has protective activity against cutaneous chemical carcinogenesis [ 170 ]. Examples of plant extracts containing phenolic compounds with anti-apoptotic properties are the extracts from Garcinia mangostana L. (mangosteen) [ 174 ], propolis [ 175 , 176 , 177 , 178 , 179 ], and Phyllanthus [ 180 , 181 , 182 , 183 , 184 , 185 ] (it also has the ability to induce cell necrosis [ 186 ]).…”
Section: Skin Diseasesmentioning
confidence: 99%
“…Another study by Kaur and co-workers showed that eugenol has protective activity against cutaneous chemical carcinogenesis [ 170 ]. Examples of plant extracts containing phenolic compounds with anti-apoptotic properties are the extracts from Garcinia mangostana L. (mangosteen) [ 174 ], propolis [ 175 , 176 , 177 , 178 , 179 ], and Phyllanthus [ 180 , 181 , 182 , 183 , 184 , 185 ] (it also has the ability to induce cell necrosis [ 186 ]).…”
Section: Skin Diseasesmentioning
confidence: 99%
“…The test substance SCF contained five major ingredients possessed the potential with joint care. Despite the safety assessment of hydrolyzed chicken sternal cartilage extract, calcium citrate, mangosteen extract, turmeric extract and soybean extract by themselves have been investigated [30] , [31] , [32] , [33] , the genotoxicity and 28-day oral toxicity of SCF containing them have not been verified. However, the uncertain cross-reactivity among these included ingredients cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, soy isoflavones by themselves had no effects on the induction of bone marrow chromosomal aberration and micronuclei in vivo , but could antagonize the benzo[a]pyrene-induced genotoxicity [31] . The leaf ethanoic extracts of mangosteen have been found to induce genotoxicity and apoptosis in B16-F10 melanoma cells [30] . In contrast, our genotoxicity results suggest that the mixture of these ingredients, including the leaf ethanoic extracts of mangosteen in SCF does not induce genotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…G. mangostana leaves contain polyphenolic major role in the prevention of various diseases [8]. Juice of G. mangostana contains polyphenolic compound such as flavonoid and tannin [9].…”
Section: Resultsmentioning
confidence: 99%
“…The leaves of G. mangostana are proven to have high phenolic compounds and have the potential as antibacterial and antitumor activity [7]. Juice of leaves of G. mangostana was shown to have free radical scavenging activity against α,α-diphenylβ-picrylhydrazyl (DPPH) radicals with IC 50 19 ppm [8]. The results of the previous research show the great potential as of G. mangostana.…”
Section: Introductionmentioning
confidence: 99%